An evaluation of HSPF and SWMM for simulating streamflow regimes in an urban watershed. (August 2019) - Nayeb Yazdi, Mohammad; Ketabchy, Mehdi; Sample, David J.; Scott, Durelle; Liao, Hehuan
Abstract: Hydrologic models such as the Storm Water Management Model (SWMM) and the Hydrologic Simulation Program-Fortran (HSPF) are widely used to evaluate the impacts of urban development on watersheds and receiving waters. We compare the ability of these two models at simulating streamflow, peak flow, and baseflow from an urban watershed. The most sensitive hydrologic parameters for HSPF were related to groundwater; for SWMM, it was imperviousness. Both models simulated streamflow adequately; however, HSPF simulated baseflow better than SWMM, while, SWMM simulated peak flow better than HSPF. Global Sensitivity Analysis showed that variability of streamflow for SWMM was higher than that of HSPF, while variability of baseflow for HSPF was greater than that of SWMM. Further, analysis of extreme storm events indicated that the runoff coefficient for SWMM was slightly greater than HSPF for recurrence intervals of 1, 2, 5, and 10-yr.; the opposite was the case for recurrence intervals greater than 10 yrs. Graphical abstract: Image 107955 Highlights: We modeled streamflow using HSPF and SWMM for an urban watershed. SWMM and HSPF simulated streamflow adequately. SWMM was better at predicting peak flow, HSPF was better at predicting baseflow. HSPF was sensitive to groundwater parameters; SWMM to imperviousness. During extreme events, the runoff coefficient for SWMM was slightly greater.